2009
DOI: 10.1161/hypertensionaha.108.120642
|View full text |Cite
|
Sign up to set email alerts
|

D 1 -Like Receptors Regulate NADPH Oxidase Activity and Subunit Expression in Lipid Raft Microdomains of Renal Proximal Tubule Cells

Abstract: Abstract-NADPH oxidase (Nox)-dependent reactive oxygen species production is implicated in the pathogenesis of cardiovascular diseases, including hypertension. We tested the hypothesis that oxidase subunits are differentially regulated in renal proximal tubules from normotensive and spontaneously hypertensive rats. Basal Nox2 and Nox4, but not Rac1, in immortalized renal proximal tubule cells and brush border membranes were greater in hypertensive than in normotensive rats. However, more Rac1 was expressed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 45 publications
4
51
0
Order By: Relevance
“…Under basal conditions, both gp91 phox and p22 phox are located in LRs. Disruption of lipid rafts with MßCD allowed the NADPH oxidase subunits (gp91 phox and p22 phox ) to move from raft to non-raft positions in the membrane; this finding is similar to previous reports (51,52). These results suggest that LRs play a pivotal role in the regulation of NADPH oxidase.…”
Section: Discussionsupporting
confidence: 89%
“…Under basal conditions, both gp91 phox and p22 phox are located in LRs. Disruption of lipid rafts with MßCD allowed the NADPH oxidase subunits (gp91 phox and p22 phox ) to move from raft to non-raft positions in the membrane; this finding is similar to previous reports (51,52). These results suggest that LRs play a pivotal role in the regulation of NADPH oxidase.…”
Section: Discussionsupporting
confidence: 89%
“…In the resting state, NOX2 and p22 phox are closely associated with each other in non-LR parts of the cell. Upon activation, they move into LRs and assemble together with the cytosolic activators, p47 phox and p67 phox , thereby forming the active NOX2 enzyme complex that generates superoxide using NADPH (36). Little information was available as to whether NOX4 also moves from the cytoplasm into LRs and, if so, whether this translocation is required for NOX4 to increase ROS generation in adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Some proteins are reported to become activated when they move into LRs (36). To determine whether NOX4 is translocated to LRs following exposure of adipocytes to high glucose or palmitate, we isolated LRs by ultracentrifugation.…”
Section: Nadph Content In Adipocytes Ismentioning
confidence: 99%
“…20 In cells of the proximal tubule, the NADPH oxidase components Nox2, Nox4, and Rac1 are expressed and even further induced by hypertension. 21 Interestingly, a role for lipid rafts in controlling NADPH oxidase activity in the proximal tubule has been suggested through an action on the oxidase activator Rac1: under nonstimulated conditions, membrane-bound Rac1 appears to be associated with lipid rafts. Destruction of rafts by cholesterol depletion activates the ROS formation from Nox2 and Nox4 NADPH oxidases in human proximal tubule cells.…”
Section: Nadph Oxidases In Renal Hypertensionmentioning
confidence: 99%
“…22 Importantly, it was observed that dopamine D1 receptor agonists also release Rac1 from lipid rafts and thereby induce an agonist-stimulated ROS production in the kidney. 21 However, it should be mentioned that overexpression studies failed to link Rac1 with Nox4 activation. 23,24 Under the latter condition, Nox4 is, however, also predominantly observed in the endoplasmic reticulum, 25 and it is currently unknown whether interacting proteins as are present in smooth muscle cells 26 associate Nox4 with lipid rafts in the kidney.…”
Section: Nadph Oxidases In Renal Hypertensionmentioning
confidence: 99%